Multimedia Simulation Model on Basic Electricial and Electronics Subjects for Vocational Secondary School - Ningrum, Aria Setia; Muslim, Suyitno; Siregar, Eveline (Journal of Education Reseach and Evaluation, 2022)
Learning conditions during this pandemic have limited direct teacher and student meetings. Online learning in SMK has several obstacles, such as the lack of appropriate learning media, which impacts student learning outcomes. This study aims to produce a simulation model of multimedia products in Basic Electrical and Electronics subjects in Vocational Schools. This type of research is development. This study uses the Bergman & Moore development model. The feasibility test was obtained based on expert studies conducted by material experts and media and learning design experts. The data collection technique used a formative evaluation instrument. This product development uses quantitative data analysis techniques and qualitative data analysis techniques. The instrument used to collect data is a questionnaire. The feasibility test results show that the multimedia with the simulation model developed is in the very feasible category with an average value of 83.7%. The effectiveness test was conducted by giving pre-test and post-test to class X SMK students with analysis using the N-Gain formula. The effectiveness test results showed that the average score of students before using multimedia was 51.33 and after using multimedia was 78.67. It was concluded that learning using multimedia could improve student learning outcomes. Multimedia can make it easier for students to understand learning materials.